ANALISIS STRATEGI PEMERINTAH DALAM PENGELOLAAN SUMBER DAYA ALAM BATU BARA DI KABUPATEN TANAH LAUT BERBASIS MANAJEMEN STRATEGIK DALAM PERSPEKTIF EKONOMI SYARIAH - Agus Purnomo; Ibrahim Hasan (Research Institute and Community Engagement of IAIN MADURA, 2017)
This research is motivated by the management of coal resources in Tanah Laut districts based on strategic management in the islamic economic perspective. The purpose of this study is to identify, examine, and find new perspectives in research analysis of government strategies in the management of coal resources 2016 based on strategic management in the economi perspective of islam.Research method used in this research is kind of mixed research. In this study researchers used quantitative data to determine the potential of minerals, coal production per year, and so on. The qualitative method in this study is intended to describe the constraints or impacts of natural resource management in Tanah Laut regency districts to know which strategies to use, it is explored through observation, interview, and documentation.Through this research, it is known that, based on the results of interviews to the energy and mineral resources department, the government’s strategy is to utilize the human resources of quality and professional and the use of modern technology to utilize resoursces and reserves of their coal.